Lack of RAAS inhibition by high-salt intake is associated with arterial stiffness in hypertensive patients. (December 2014) - Kotliar, Carol; Kempny, Pablo; Gonzalez, Sergio; Castellaro, Carlos; Forcada, Pedro; Obregon, Sebastián; Cavanagh, Elena; Chiabaut Svane, Jorge; Casarini, Maria Jesus; Rojas, Mercedes; Inserra, Felipe
Hypothesis/introduction: The relationship between salt intake, blood pressure and RAAS activation is still controversial, being that both high- and low-salt intakes are associated with cardiovascular events in a J-shaped curve pattern. We hypothesized that different patterns of RAAS response to dietary salt intake among hypertensives could be identified, while vascular damage would be related to high-salt intake plus absence of expected RAAS inhibition. Objective: We aim to assess the relationship between sodium intake, RAAS and vascular stiffness in hypertension. Materials and methods: We screened 681 hypertensive patients for urinary/plasma electrolytes, renin, aldosterone and pulse wave velocity (PWV) under their usual salt intake level. Results: After applying exclusion criteria, an inverse relation between urinary sodium and RAAS was observed in the 300 remaining subjects. Additionally, four types of response were identified: 1) Low (L) sodium (S)-Low RAAS, 2) LS-High (H) SRAAS, 3) HS-Low RAAS, 4) HS-High RAAS. We found no differences in age/BP among groups, but type 4 response individuals included more females and a higher pulse wave velocity. Conclusions: We showed a) an inverse salt-RAAS relation, b) an association between HS plus high RAAS with increased PWV that could identify a higher-risk hypertensive condition.